Chelated Forms of Trace Elements as a Promising Solution for Improving Soybean Symbiotic Capacity and Productivity Under Climate Change - Tetiana Nyzhnyk; Sergii Kots (Frontiers in Bioscience-Elite)
Background: The tolerance and productivity of soybeans under the current climate change conditions can be increased by providing these crops with the necessary macro- and microelements. This can be achieved using effective Bradyrhizobium strains for seed inoculation and adding chelated trace elements. Methods: Soybean Bradyrhizobium japonicum symbioses were cultivated by adding chelates of trace elements, such as iron (Fe), germanium (Ge), and molybdenum (Mo), to the culture medium, after which microbiological and biochemical analyses were performed. Results: The addition of chelated forms of Fe or Ge to the Bradyrhizobium culture medium promoted a change in the pro-oxidant-antioxidant balance in soybean nodules under different water supply conditions. This is due to the production of hydrogen peroxide in the nodules (an increase of 12.9%), as well as a twofold increase in the ascorbate peroxidase activity and a decrease in the levels of superoxide dismutase (by 40%) and catalase (by 50%) under water stress. Stimulation of nodulation and nitrogen fixation in soybeans (by 40.1 and 73.0%) and an increase in grain productivity (by 47.5 and 58%) were observed when using Bradyrhizobium inoculant containing Fe or Ge chelates. The inoculation of soybeans with Bradyrhizobium modified using Mo chelate causes similar changes in antioxidant processes as Fe or Ge chelates, but the soybean symbiotic capacity decreases under water stress. Conclusion: Chelated forms of Fe or Ge as additional components in the Bradyrhizobium culture medium are effective in regulating the antioxidant status of soybeans under drought conditions and can simultaneously contribute to increased nitrogen fixation and grain productivity. These findings are important in expanding the current technologies used to grow this legume in risky farming areas caused by climate change.